2000
DOI: 10.4049/jimmunol.165.8.4704
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP and TNF-α Synergize in the Activation and Maturation of Human Dendritic Cells

Abstract: Extracellular ATP mediates numerous biological activities by interacting with plasma membrane P2 purinergic receptors. Recently, P2 receptors have been described on dendritic cells (DC), but their functional role remains unclear. Proposed functions include improved Ag presentation, cytokine production, chemotaxis, and induction of apoptosis. We investigated the effects of ATP and of other P2 receptor agonists on endocytosis, phenotype, IL-12 secretion, and T cell stimulatory capacity of human monocyte-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
146
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(158 citation statements)
references
References 37 publications
10
146
0
2
Order By: Relevance
“…Nucleotides are known to activate a variety of immune cells (67)(68)(69)(70). We observed that ADP induced calcium signals in GM-CSF/IL-4 differentiated myeloid DCs, but not in T cells or the B cell lines (Fig.…”
Section: Rhuhsp70-mediated Augmentation Of Cross-presentation Is Proxmentioning
confidence: 60%
“…Nucleotides are known to activate a variety of immune cells (67)(68)(69)(70). We observed that ADP induced calcium signals in GM-CSF/IL-4 differentiated myeloid DCs, but not in T cells or the B cell lines (Fig.…”
Section: Rhuhsp70-mediated Augmentation Of Cross-presentation Is Proxmentioning
confidence: 60%
“…The involvement of the purinergic system in DC functionality was equally confirmed by assessing the maturation status based on the levels of DC surface markers. The implication of P2 receptors in DC maturation was already suggested by Schnurr et al in showing that activation and maturation of DCs was blocked by suramin [133]. Later studies showed that in combination with TNF-α, ATP increased the expression of the DC surface markers CD80, CD83, and CD86 confirming a maturation-promoting effect [123].…”
Section: Dendritic Cellsmentioning
confidence: 71%
“…Several molecules have been identified, which, when released from injured or dying eukaryotic cells, activate innate immunity. These endogenous activators of innate immunity are evolutionarily conserved proteins or nucleotides with the common feature of being "foreign" to the extracellular environment in a normal tissue (Basu et al, 2000;Sauter et al, 2000;Schnurr et al, 2000;Termeer et al, 2000;Somersan et al, 2001). The novelty of our data in this context is that such endogenous activators may also play a role in CNS injury.…”
Section: Discussionmentioning
confidence: 90%